Development of 4C's Instruments on Aswaja Materials with National Value - Fitri Umardiyah; Nur Sihabudin Achmad (SCHOOLAR: Social and Literature Study in Education, 2021)
This study aims to develop a valid and practical learning module. This research is a research and development using the ADDIE Method (Analysis, Design, Development, Implementation, and Evaluation). The analysis technique of this research uses quantitative data in the form of scores from the validator, the value of the teacher's response, the value of the student's response to the video learning media in the form of a questionnaire score. Qualitative data in the form of interviews with educational practices or private teachers and nationalities and criticism of suggestions from validators. The results of this study resulted in a product in the form of a 4C-based learning module, namely critical thinking skills, collaborative skills, communication skills and creative skills on personal and nationality material. The feasibility of the product is based on the results of the validation test and practicality test. Assessment by material experts got a score of 81% with a very valid or proper classification. The results of the teacher's response questionnaire scored 87% with a very valid classification or very feasible to use. The results of the student response questionnaire scored 81% with a very practical classification. Based on these results, it can be said that the 4C-based learning modules are critical thinking skills (Critical thinking skills), collaboration skills (Collaborative Skills), communication skills (Communicative Skills), and creative skills (Creative Skills) on personal and nationality materials that are suitable for use.